"My Dog Deafened Me!": Case Report of Capnocytophaga canimorsus Infection and Literature Review. (25th August 2018) - Cadre, Barbara; Al Oraimi, Mouna; Grinholtz‐Haddad, Julia; Benkhatar, Hakim
Abstract : Capnocytophaga canimorsus infection is an emerging zoonotic disease that could cause meningitis and subsequent sensorineural hearing loss (SNHL), especially in the immunocompromised population. It is a gram‐negative rod that belongs to the normal oral flora of dogs and cats and may be transmitted to humans by biting or licking. Our case report and literature review showed that this postmeningitic SNHL has distinct features from common bacterial meningitis‐related SNHL. We therefore discuss the diagnostic, therapeutic, and preventive aspects of this uncommon cause of SNHL. Because it is now the second‐most common dog‐bite transmitted pathogen, otolaryngologists are more likely to encounter this zoonotic disease and should be aware of its characteristics. Laryngoscope, 129:41–43, 2019